2023
DOI: 10.1039/d2ee03956g
|View full text |Cite
|
Sign up to set email alerts
|

Cobaloximes: selective nitrite reduction catalysts for tandem ammonia synthesis

Abstract: Herein, we demonstrate cobaloxime as a bio-inspired molecular platform for exclusive ammonia synthesis via electrocatalytic NO2- reduction (eNO2-RR), which attained 98.5% Faradic efficiency (FE) under close-to-neutral conditions. Mechanistic studies illustrated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…In Sections and 3.2, the nitrate reduction performance of the electrocatalyst and the nitrogen fixation ability of the DBD plasma reactor are evaluated, respectively. The previously published work treated the two processes separately, which makes it difficult to realize the ammonia synthesis continuously and stably. ,, Meanwhile, the inherent shortcomings of H-type batch reactors also cannot meet the requirement for the demonstration of industrial application. Therefore, as shown in Figure S1, the coupled process of plasma nitrogen fixation with the electrocatalytic ammonia synthesis is designed to realize the sustainable production of ammonia from air to product.…”
Section: Resultsmentioning
confidence: 99%
“…In Sections and 3.2, the nitrate reduction performance of the electrocatalyst and the nitrogen fixation ability of the DBD plasma reactor are evaluated, respectively. The previously published work treated the two processes separately, which makes it difficult to realize the ammonia synthesis continuously and stably. ,, Meanwhile, the inherent shortcomings of H-type batch reactors also cannot meet the requirement for the demonstration of industrial application. Therefore, as shown in Figure S1, the coupled process of plasma nitrogen fixation with the electrocatalytic ammonia synthesis is designed to realize the sustainable production of ammonia from air to product.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the electrocatalytic nitrate (NO 3 − )/nitrite (NO 2 − ) reduction reaction has shed new light on renewable NH 3 synthesis as NO x − exhibits substantially increased solubility in water and lower cleavage energy compared to N 2 . 13–15 The stable supply of NO 3 − and NO 2 − is a crucial factor for achieving electrocatalytic green ammonia generation. It might be advisable to obtain NO x − from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…25 Wu et al discovered that the catalyst composed of cobaloximes and multi-walled carbon nanotubes achieved an NH 3 yield of about 115 μmol h −1 , and a high NH 3 FE above 95% at −0.5 V vs. RHE. 26 Liu and co-workers recently reported that the FeP nanoarrays on a Ti plate can selectively reduce NO 2 − to NH 3 with an NH 3 FE of 82.5%. 16 Although some achievements have been made in Fe or Co-based nitrite reduction electrocatalysts, there is still much room for performance improvement.…”
mentioning
confidence: 99%